Extended Theory of Planned Behavior Model to Predict Factors Affecting the Behavior of Eating Halal Food (Case Study of Santri Tahfidz Pondok Pesantren Al Muayyad Surakarta) - Nailil Muna; Muhammad Fauzan Aminudin; Daryanto Daryanto; Fikrina Faraidi Fardani; Endah Kristiani; Nur Rahmawati; Adhista Setyarini (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study examined the characteristics that impact tahfidz students' food choices at Al Muayyad Islamic Boarding School in Surakarta, particularly halal food intake. This is quantitative descriptive research. Halal food purchases are mainly influenced by the Extended Theory of Planned Behavior model. Awareness, behavioral habits, religious self-identity, moral commitments, and trust also affect this technique. The sample included Al Muayyad Islamic Boarding School pupils memorizing the Qur'an. Data collection techniques with random sampling method through distributing questionnaires. Furthermore, the data analysis technique uses the SPPS version 26.0 application with multiple linear regression tests. Moral obligation has a significant positive effect on halal food consumption behavior, subjective norm or subjective norm has a significant negative relationship. Other components or factors, do not have a significant influence on the decision to consume halal food for students even though they have a positive relationship.